Arrival of the invasive amphipod Grandidierella japonica to the Mediterranean Sea. Issue 1 (December 2016) - Marchini, Agnese; Ferrario, Jasmine; Nasi, Emanuele
Abstract Background In the marine environment, shipping is globally acknowledged as the major vector of introduction of organisms outside their native range. We surveyed harbours and marinas in the Western Mediterranean Sea for occurrence of non-indigenous species. Results More than 200 specimens of the Japanese amphipodGrandidierella japonica were collected in 2013 from the docks of the marina of Viareggio (Tuscany, Tyrrhenian Sea). This is the first record of this species for the Mediterranean Sea. Conclusions G. japonica was previously introduced elsewhere by oyster trade and shipping; in the case of Viareggio, where no aquaculture facilities or international shipping occur, recreational boating is the only likely vector of introduction. In Europe, G. japonica is currently confined by a few localities, mainly estuaries, enclosed bays and brackish water areas, but its successful history of invasion in the Pacific coasts of North America suggests that a further spread can be expected in the Mediterranean Sea as well.